Investigation of stability of slopes under drawdown conditions - Berilgen, Mehmet M. (ELSEVIER SCI LTD, 2007)
Because of the rapid drawdown there will be a decrease in the slope stability which might lead to instability in slopes that do not have sufficient level of safety against failure. This paper presents an investigation of slope stability during drawdown depending on the soil permeability, drawdown rate and drawdown ratio, considering the nonlinear material and loading conditions. For this purpose, a coupled transient seepage and deformation analyses (including consolidation), together with the stability analysis, were performed using the FEM for submerged slopes. Nonlinear elasto-plastic behavior of the slope soil is taken into account while analysis of the generation and dissipation of pore pressure is carried out. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: slope stability; seepage; FEM modeling; rapid drawdown; Computer Science; Engineering; Geology